The Rhetorical Biopower of Eugenics: Understanding the Influence of British Eugenics on the Nazi Program - Caleb, Amanda M. (Conatus - Journal of Philosophy, 2019)
The relationship between the British and Nazi eugenics movements has been underexamined, largely because of the more obvious ties between the American and Nazi programs and the lack of a state-sponsored program in Britain. This article revisits this gap to reinsert the British eugenics movement into the historiography of the Nazi program by way of their shared rhetoric. To do this, I employ Foucault’s concepts of biopower and power/knowledge, arguing that biopower exists in rhetorical constructions of power and identity, which the eugenics movements employed at national and individual levels to garner support and participation, particularly from women. The article is not an exhaustive account of the rhetorical overlaps between the two movements, but rather serves as a model of how one might understand eugenics as a rhetoric of biopower.